Ideas and Innovation in East Asia - Brahmbhatt, Milan; Hu, Albert (World Bank, Washington, DC, 2012)
The generation, diffusion, absorption and application of new technology, knowledge or ideas are crucial drivers of development. This paper surveys the diverse approaches to innovation adopted by East Asian economies, the problems faced and outcomes achieved, as well as possible policy lessons. Knowledge flows from advanced countries remain the primary source of new ideas in developing economies. The authors evaluate the role of three main channels for knowledge flows to East Asia - international trade, acquisition of disembodied knowledge and foreign direct investment. The paper then looks at the exceptionally fast growth in domestic innovation efforts in Korea, Taiwan (China), Singapore and China, drawing on information about R&D as well as original analysis of patent and patent citation data. Citation analysis shows that while East Asian innovations continue to draw heavily on knowledge flows from the US and Japan, citations to the same or to other East Asian economies are quickly rising, indicating the emergence of national and regional knowledge stocks as a foundation for innovation. A last section pulls together findings about policies and institutions to foster innovation, under three heads: the overall business environment for innovation (macroeconomic stability, financial development, openness, competition, intellectual property rights and the quality of communications infrastructure), human capital development, and government fiscal support for innovation.